THE INFLUENCE OF ACCESSIBILITY, SERVICE, AND KNOWLEDGE OF SHARIA ACCOUNTING ON INTEREST TO SAVE IN SHARIA BANK (CASE STUDY OF UPI YPTK PADANG STUDENTS) - Harmelia Harmelia; Mutia Seplinda; Yonna Anggayu Putri (Jurnal Ekonomi, 2022)
This study uses primary data, namely through a questionnaire (questionnaire) using a Likert scale measurement scale. The sample in this study was 100 respondents distributed to UPI YPTK Padang students randomly. The analytical method used is a quantitative analysis using multiple linear regression with the help of SPSS version 25. The research results obtained indicate that accessibility and knowledge accountancy Sharia has a positive and significant effect on the intention to save UPI YPTK Padang students in Islamic banks with a t-count of 2.022 with a significance of 0.046 and a t-count of 3.136 with a significance of 0.002. While the service does not affect significantly the interest in saving UPI YPTK Padang students in Islamic banks with a t-count value of 0.044 with its significance value was 0.965.